Determining factors in becoming a sustainable smart city: an empirical study in Europe - Gil, M. T. N.; Carvalho, L.; Paiva, I. (Economics and Sociology, 2020)
This paper aims firstly to identify differences and similarities between cities according to the activities which are necessary to become a smart city and secondly to identify relevant factors that could influence positions in the smart cities ranking. To achieve these goals, this study uses a quantitative analysis applied to 73 European cities to identify the factors that influence differences between smart cities. The results suggest the formation of clusters around European smart cities and also that cities located geographically in the west of Europe and with governance by women present higher levels in the European Smart Cities rankings.